Computed tomography appearance of the thymus and anterior mediastinum in active Cushing's syndrome. - Hanson, J; Sohaib, SA; Newell-Price, J; Islam, N; Monson, J; Trainer, P; Grossman, A; Besser, G; Reznek, R (1999)
Computed tomography (CT) evaluation of the thymus and anterior mediastinum is an important aspect of the investigation of patients with ACTH-dependent Cushing's syndrome in order to exclude an ACTH-secreting carcinoid tumor. We have reviewed the CT imaging of the thymus and anterior mediastinum in a series of 85 patients (55 females; median age 41, range 7-77 yr) with active Cushing's syndrome as there are few data on the range of appearances in hypercortisolemic states. One patient had a thymic carcinoid tumor (24 x 18 mm). Of the others, 28/84 (33%) patients showed thymic remnant tissue, consisting of either nodule(s) at least 5 mm diameter (n = 21, mean diameters 12.5 +/- 5 x 9.6 +/- 4 mm), or triangular bilobed glands (n = 7, mean thickness of the body, right and left limbs 25 +/- 7, 14 +/- 3, and 12 +/- 5 mm). Thymic involution appeared in 56/84 (67%) patients, ranging from small nodule(s) of less than 5mm diameter to linear soft tissue strands and complete fatty replacement. Patients with thymic remnant tissue were younger than those with thymic involution (P < 0.05). The thymic carcinoid tumor could be distinguished from remnant tissue on the basis of age and size. The presence of anterior mediastinal nodule(s) in hypercortisolemia need not imply the presence of a thymic carcinoid tumor, although in older patients this should arouse suspicion.